2016
DOI: 10.1152/ajpheart.00295.2015
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated cardiac remodeling in desmoplakin transgenic mice in response to endurance exercise is associated with perturbed Wnt/β-catenin signaling

Abstract: Arrhythmogenic ventricular cardiomyopathy (AVC) is a frequent underlying cause for arrhythmias and sudden cardiac death especially during intense exercise. The mechanisms involved remain largely unknown. The purpose of this study was to investigate how chronic endurance exercise contributes to desmoplakin (DSP) mutation-induced AVC pathogenesis. Transgenic mice with overexpression of desmoplakin, wild-type (Tg-DSP(WT)), or the R2834H mutant (Tg-DSP(R2834H)) along with control nontransgenic (NTg) littermates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
3
35
0
1
Order By: Relevance
“…Similar findings were observed in plakophillin-2 (5) and desmoplakin deficient mice (16), suggesting that exercise training accelerates ARVD/C development in mutation carriers. Whether genotype to phenotype development is also accelerated in other genetic cardiac diseases such as hypertrophic cardiomyopathy and long QT syndrome is currently unknown.…”
Section: Genetic Vulnerability To Exercisesupporting
confidence: 77%
“…Similar findings were observed in plakophillin-2 (5) and desmoplakin deficient mice (16), suggesting that exercise training accelerates ARVD/C development in mutation carriers. Whether genotype to phenotype development is also accelerated in other genetic cardiac diseases such as hypertrophic cardiomyopathy and long QT syndrome is currently unknown.…”
Section: Genetic Vulnerability To Exercisesupporting
confidence: 77%
“…In contrast, 8x dyn-EHTs formed using DSPmut cardiomyocytes resulted in tissue lengthening and reduced contractile stress generation. Furthermore, in DSPmut tissues we found reduced amount and expression of desmosomes compared to control, which has also been observed in patients and small animal studies with desmosomal defects (5,71). Taken together, these findings suggest that 3D dynamic mechanical loading of EHTs may be better suited to investigate heart diseases with a cardiomyocytejunctional or cytoskeletal component.…”
Section: Discussionsupporting
confidence: 82%
“…As proof-of-concept, we chose to study ACM, where epidemiological data and animal models have indicated that enhanced mechanical loading, i.e. exercise, can accelerate disease progression in patients (5,(41)(42)(43)(44). To understand the impact of 2D versus 3D culture, we first investigated 2D monolayers of hiPSC-derived cardiomyocytes subjected to mechanical stretch.…”
Section: Dynamic 8x Loading Reveals a Disease Phenotype Based On A Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Wnt pathway perturbation, due to reduced AKT and GSK3β activation, has been recently associated to exercise-induced acceleration of AC phenotype in mice overexpressing a mutant form of desmoplakin and exposed to a daily running [ 95 ]. The identification of a Wnt pathway activator as the molecule that can rescue the features of the AC phenotype both in a zebrafish and in additional mouse models [ 96 , 97 ] strongly supports the association between AC and suppression of this signaling pathway.…”
Section: Introductionmentioning
confidence: 99%